Sexual violence in college students in Chile - Jocelyn A. Lehrer; Vivian L. Lehrer; Evelyn Lilian Lehrer; Pamela Oyarzun (Institute for the Study of Labor (IZA), 2007)
Young women's experiences of sexual victimization can have far-reaching consequences, including unwanted pregnancy and increased risk of psychological, sexual, and reproductive health difficulties; these experiences can also limit young women's ability to achieve their educational potential. To date, no quantitative studies have examined sexual violence among college students in Chile. To address this gap, an anonymous survey was administered to students enrolled in General Education courses at a major public university in Santiago (n=455 female students). Rape, attempted rape, and other types of sexual victimization were reported by 9.4%, 6.2%, and 15.6% of respondents, respectively, as the most severe event experienced since age 14; 17.2% reported some form of sexual victimization in the past 12 months alone. Estimates based on ordered logit models show that low parental education, childhood sexual abuse, and witnessing inter-parental violence are associated with increased odds of sexual victimization since age 14; attendance to religious services and living with the parents while attending college have protective effects. The findings indicate a need to further investigate the prevalence of and risk factors for sexual violence in Chilean college students, and to begin to develop and evaluate theory-based programs to prevent and respond to this public health concern.
Keywords: 370; Sexual victimization; gender based violence; Sexuelle Belästigung; Studierende; Bildungsniveau; Chile